2009
DOI: 10.1007/s11596-009-0601-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent assay of microbial ATP in postmortem tissues for the estimation of postmortem interval

Abstract: To study the relationship between changes of microbial ATP in four kinds of murine tissues and the postmortem interval (PMI), healthy SD rats were sacrificed and their muscles, livers, spleens and kidneys were sampled at different postmortem intervals. The concentration of microbial ATP was detected using bioluminescent assay and the data was statistically analyzed. The concentration of microbial ATP in muscle increased with PMI time. The peak appeared at the 7th day after death, and at the 10th day, microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Other methods could also be used to assess the molecular changes of muscles or OMI marker [24,25] , but they all consumed much time. Taking into consideration of results of the present study, we suggest that the substructure differences revealed from the FTIR spectral intervals that present a discrimination potential between protein analyses should be considered in the identification of amide types for analyzing infarct scar formation and assembly in histological sections.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods could also be used to assess the molecular changes of muscles or OMI marker [24,25] , but they all consumed much time. Taking into consideration of results of the present study, we suggest that the substructure differences revealed from the FTIR spectral intervals that present a discrimination potential between protein analyses should be considered in the identification of amide types for analyzing infarct scar formation and assembly in histological sections.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other methods can be used to estimate the PMI for human remains found on land, for example Megyesi's Total Body Score (TBS), 2 Gelderman's Total Decomposition Score (TDS), 29 entomology, 5,[30][31][32] volatile fatty acids in soil 33,34 and ATP (Adenosine Triphosphate) determination from the brain, liver, spleen, kidney and muscle. [35][36][37] The former two methods are decomposition scoring methods which describe the decomposition process. With these methods, the PMI can be estimated using the accumulated degree days (ADD).…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Nielsen stated that a relatively even temperature and low air flow velocity in room was controlled by FADS [5]. In 2009, Liu Chao used the FLUENT software to simulate the air distribution of FADS and the ordinary air conditioning system [6]. In 2011, Chen Fu-jiang studied FADS by numerical simulation and experimental.…”
Section: Introductionmentioning
confidence: 99%